Determinants of Saving Decisions at Indonesian Islamic Banks During the COVID-19 Pandemic - Muhammad Afifuddin Abdurrosyid Kamil; Ranti Wiliasih; Mohammad Iqbal Irfany (goodwood publishing, 2022)
Purpose: This study aims to determine the characteristics and factors influencing the decision to save at Islamic banks, during the COVID-19 pandemic. Research methodology: The sample used in this study amounted to 400 participants, which were collected by online questionnaire. A logistic regression was also employed to estimate the influence of independent variables on the saving decisions of customers. This was accompanied by the implementation of descriptive analysis, to determine the characteristics of Islamic bank customers during the pandemic. Results: The characteristics of the participants were dominated by people aged 17-25, with the majority of them residing in West Java and working as a student. Besides this, data were also analyzed by using logistic regression analysis. Based on the results, several factors influenced the saving decisions of Islamic bank customers. In this case, evaluation and strategy were carried out to increase customer interest through knowledge of the types and benefits of Islamic savings. Limitations: This study was limited to the analysis of the factors influencing the saving decisions of Islamic bank customers during COVID-19. The contribution derived was also related to the saving demands of customers in Islamic banking. Contribution: The results highlighted the characteristics of Islamic bank customers during the pandemic, as reference material for banking managers to increase interest in their financial products. Originality: Based on the logistic regression, religiosity, knowledge, promotion, location, and age positively/significantly affected saving decisions at Islamic banks during the COVID-19 pandemic. This indicated that Islamic banking was not stuck in the market segment of the Muslim community, regarding the promotion of their products. In addition, promotion quality should be essentially improved, accompanied by the maintenance of business ethics and image as an Islamic bank.